Pengaruh Kepemimpinan, Budaya Organisasi, Kualitas Pelayanan Terhadap Kepuasan Pelanggan PT. Astra Internasional, Tbk. Daihatsu Cabang Malalayang - Siwu, Priskilla Natalia; Pio, Riane J; Liando, Daud Markus (JURNAL ILMIAH SOCIETY, 2016)
This research aims to know the influence of leadership against the leadership, the influence of organizational culture on quality of service, leadership influence towards customer satisfaction, the influence of organizational culture on quality of service, the influence of organizational culture towards customer satisfaction, influence the quality of service towards customer satisfaction. Research methods using this type of quantitative research. Analysis tools using Structural Equation Modeling (SEM). The conclusion that the leadership will have an impact on the high culture of the Organization and influence on quality of service, but not directly influential leadership towards customer satisfaction, organizational culture influence on quality of service and customer satisfaction, and quality of service to customer satisfaction in the PT. Astra International Keywords : leadership, organizational culture, service quality,